Characterization of microminipig as a laboratory animal for pharmacological study by analyzing bepridil-induced cardiovascular responses - Yoshio Nunoi; Mihoko Hagiwara-Nagasawa; Ryuichi Kambayashi; Ai Goto; Koki Chiba; Takeshi Wada; Hiroko Izumi-Nakaseko; Akio Matsumoto; Yoshinori Watanabe; Atsushi Sugiyama (Elsevier, 2020)
Since microminipig is becoming attractive model for various cardiac electropharmacological applications, which may meet consideration of 3Rs. We characterized microminipigs by analyzing how multi-ionic channel inhibitor bepridil may affect their in situ hearts in comparison with dogs. Bepridil in doses of 0.3 and 3.0 mg/kg were intravenously administered over 10 min under halothane anesthesia (n = 4). Microminipigs may be less sensitive for ICaT inhibition of bepridil, whereas they are more responsive to INa, IKr and IKs suppression than dogs. This information would help predict cardiovascular effects of a drug in patients with the remodeled hearts having similar electrophysiological profile to microminipigs. Keywords: Microminipig, ICaT inhibitory action, IKs suppression